PARTISIPASI ANGGOTA DALAM PENGEMBANGAN KELOMPOK TANI DI DESA SOATOBARU KECAMATAN GALELA BARAT - Edwin ., Maleba; Ventje V. Rantung; Welson M. M. Wangke; Yolanda P. I Rori (Sam Ratulangi University, 2015)
This study aims to determine the participation of members in the development of farmer groups in the village Soatobaru Galela District West. The research is expected to provide information regarding participation of farmer group members on farmer group development. This research was conducted in the village of Soatobaru Galela District West, North Halmahera and lasted for three months from preparation through statements commencing from April to June 2015. Data collections were using primary data and secondary data. The primary data obtained through interviews with members of farmer groups based on a list of questions that had been prepared previously. Research was using census method in both groups of farmers that farmers group One Heart with group members 26 and Melati Jaya with members of 24 people who lived in the village of Soatobaru Galela District West. Secondary data were obtained from the parties or the relevant agencies inclulding Soatobaru village office and two farmer group offices/ documentation. Member participation in the development of farmer groups in the village Soatobaru Galela District West by 5 (five) indicators, namely: Presence in the preparation of the program, activeness provide feedback or opinions in the preparation of the program, active participation in the implementation of activities within the group, activeness helps fund the group, activeness program evaluation in groups and activeness in providing input or opinion in the evaluation. Based on the results of the study found that the level of participation of members of farmers One Heart classified in the category of active, it is seen from the activity of members in the activities of farmer groups ranging from the involvement of the presence in the preparation of the program, the liveliness of their input or opinions in the preparation of the program, active participation in the implementation of activities within the group , activeness of program evaluation in the group, as well as active in providing input or opinion in the evaluation. While the level of participation of members of farmer group Melati Jaya relatively less active on five aspects because they still lack of information and lack of initiative of members of farmer groups.